The Puffin book of school stories - Ashley, Bernard; Lee, Stephen (London, Puffin, 1993)
A collection of stories about school by authors such as Noel Streatfeild, Jan Mark, Charles Dickens, Ger Duffy and Bernard Ashley. The stories take a look at starting a new term, dealing with bullying, getting out of a sticky situation and facing parents with a bad report.
Keywords: English short stories